Enhancement of the release of azelaic acid through the synthetic membranes by inclusion complex formation with hydroxypropyl-β-cyclodextrin - Manosroi J. (2014)
The aim of this study was to investigate the release rates of azelaic acid and azelaic acid-hydroxypropyl-β-cyclodextrin (HPβCD) inclusion complex through three types of synthetic membranes, namely cellophane, silicone and elastomer membranes. Solid inclusion complexes of azelaic acid-HPβCD at the molar ratio of 1:1 were prepared by coevaporation and freeze-drying methods, subsequently characterized by differential scanning calorimetry, X-ray diffractometry and dissolution studies. Solid inclusion complex obtained by coevaporation method which exhibited the inclusion of azelaic acid in the HPβCD cavity and gave the highest dissolution rate of azelaic acid was selected for the release study. Release studies of azelaic acid and this complex through the synthetic membranes were conducted using vertical Franz diffusion cells at 30°C for 6 days. The release rates of azelaic acid through the synthetic membranes were enhanced by the formation of inclusion complex with HPβCD at the molar ratio of 1:1, with the increasing fluxes of about 41, 81 and 28 times of the uncomplexed system in cellophane, silicone and elastomer membranes, respectively. The result from this study can be applied for the development of azelaic acid for topical use. © 2005 Elsevier B.V. All rights reserved.